Giving Effect of Different Natural Feed on the Growth and Survivval Fish Larvae Climbing Perch (Anabas testudinieus) - Esron Hermanto Tampubolon; Nuraini '; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in April to May 2015 in the Laboratory ofFish Hatchery and Breeding Faculty of Fisheries and Marine SciencesUniversity of Riau. The purpose of this research was to determine the effect ofdifferent natural feed on the growth and survival of fish larvae. This researchused the experimental method, while the experimental design that was usedcompletely randomized design (CRD) with 3 levels of treatment and 3repetitions. The treatments in this research are PA (natural feeding Artemia sp),PT (Feeding naturally worms Tubifex sp), and PKA (natural feeding Kutu air).The result showed that feeding kutu air naturally is the best to feed thegrowth of absolute weight that produces 0.659 grams, the growth of theabsolute length of 2.66 cm, the daily growth rate of 21.633%, while the bestsurvival rate found in the natural feeding Artemia sp is 81 %.Keywords: Natural food, Anabas testudineus, growth, and survival